2017
DOI: 10.1039/c7cc06624d
|View full text |Cite
|
Sign up to set email alerts
|

In situcharacterization of advanced glycation end products (AGEs) in collagen and model extracellular matrix by solid state NMR

Abstract: Pathological glycation of extracellular matrix modelled with 13C-labelled sugars yields unique novel atomic level NMR structural and chemical insights non-destructively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
(26 reference statements)
1
16
0
Order By: Relevance
“…Where there is additionally cell necrosis, as in the tumour setting, there is the possibility of even higher local R5P concentrations in the extracellular fluid. We have recently shown that the majority of the collagen glycation products for ribose and ribose-5-phosphate (R5P) 16,38 are, as for glucose glycation, monovalent sidechain modifications 16,38 , primarily sugar adducts and that the dominant AGEs are carboxymethyllysine (CML), carboxyethyllysine (CEL) and norpronyllysine (see Fig. S1) consistent with previous work on R5P glycation of amino acids 17 .…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Where there is additionally cell necrosis, as in the tumour setting, there is the possibility of even higher local R5P concentrations in the extracellular fluid. We have recently shown that the majority of the collagen glycation products for ribose and ribose-5-phosphate (R5P) 16,38 are, as for glucose glycation, monovalent sidechain modifications 16,38 , primarily sugar adducts and that the dominant AGEs are carboxymethyllysine (CML), carboxyethyllysine (CEL) and norpronyllysine (see Fig. S1) consistent with previous work on R5P glycation of amino acids 17 .…”
supporting
confidence: 87%
“…R5P-glycated collagen fibrils were generated as previously described 38 by incubating bovine Achilles' tendon collagen type I and either U-13 C-R5P (for NMR verification of R5P glycation products) or unlabelled R5P (for all other experiments) for six weeks to ensure equilibrium for all reactions is reached. The distribution of R5P glycation products was verified to be similar to that previously described 38 by 1D 13 C and 2D 13 C- 13 C correlation NMR spectroscopy ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid-state (SS) NMR spectroscopy has been used extensively to study challenging biological systems, [1][2][3][4][5] including large transmembrane proteins; [6][7][8][9][10][11][12][13][14] membrane fusion polypeptides; [15][16][17] protein fibrils; [18][19][20][21][22] native collagens; [23,24] polysaccharides; [25][26][27] and, more recently,R NA. [28][29][30][31][32][33][34] The application of SSNMR spectroscopy to in vivo studies is also an attractive field, [35][36][37] whichp rovides great opportunities for characterizing the cellular components of living cells [37,38] and investigating the effects of antibiotics on cells.…”
Section: Introductionmentioning
confidence: 99%
“…Where necessary to distinguish between low abundance protein, and non-protein, signals, we conrmed amino acid type assignments by comparison with ECM produced by cells cultured on media supplemented with one or a few specic amino acids, using methods already described. 4,5 Our previous analysis of bone focussed on the relatively abundant species observable with conventional ssNMR. The enhancement provided by DNP now reveals non-protein biomolecules biosynthesized from isotopically enriched amino acids and/or sugars, and their incorporation into bone.…”
mentioning
confidence: 99%